Polymer electrolyte, preparation method thereof and composite solid electrolyte
By adding polymer alcohols and beater of polymer chain to polyurethane electrolytes, the modified polyurethane of the alternative discharge is generated to solve the problem of strong crystallization of polyurethane electrolyte at room temperature, and the ion transmission capacity and mechanical performance are improved.
Patent Information
- Application Number
- CN202411498821.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
AI Technical Summary
The existing polyurethane electrolytes have strong crystallinity at room temperature, which affects the ionic conductivity. Increasing the hard segment ratio can reduce crystallinity but also reduce the dissolution ability of lithium salts, resulting in a decrease in ion conductivity.
By adding polymer alcohol and cypressic acid to the twoocyanate to the two -containing side chain, the modified polyurethane is generated, and the chain segments A in the modified polyurethane and the chain segment B alternately discharge. Crystallization is reduced, and ion transmission capacity is improved.
It reduces the crystallization of the polymer electrolyte and improves the transmission capacity of ions. At the same time, the mechanical strength and flexibility are guaranteed by regulating the density of hydrogen bonds.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a polymer electrolyte and a preparation method thereof, and a composite solid electrolyte. Background Art
[0002] With the popularity of new energy vehicles, the market demand for lithium batteries, which are the main components of new energy vehicles, is increasing. Due to the requirements of driving range, the energy density of batteries is getting higher and higher, and the safety of batteries is becoming more and more prominent. Safety is still the key factor restricting the application of lithium-ion batteries in high-power / high-energy fields. The non-liquid electrolyte used in solid-state lithium-ion batteries has higher safety than liquid electrolytes. Polymer electrolytes are a commonly used solid electrolyte, among which polyurethane can dissolve a large amount of lithium salts and has good flexibility because its soft segment can provide good ion conductivity, and hard segments and hard segments and hard segments and soft segments can form hydrogen bonds. Strong hydrogen bonding provides good mechanical properties for polymer electrolytes and has attracted widespread attention. However, the existing polyurethane has strong room temperature crystallinity, which affects the ionic conductivity. Increasing the hard segment ratio can reduce the crystallinity of polyurethane, but it will also reduce the dissolution of lithium salts, resulting in a reduction in ion conductivity. Therefore, there is an urgent need for a composite electrolyte that can solve the above problems. Summary of the invention
[0003] In order to solve the above problems, the present invention discloses a polymer electrolyte and a preparation method thereof, and a composite solid electrolyte. The technical solution of the present invention is implemented as follows:
[0004] The first aspect of the present invention is to provide a polymer electrolyte, wherein the polymer electrolyte comprises a modified polyurethane; the modified polyurethane comprises a segment A of a polyol and a segment B formed by the reaction of a diisocyanate and ricinoleic acid, wherein the segment A and the segment B are arranged alternately;
[0005] Wherein, the polyol is a polyaliphatic polyol;
[0006] The monomers of the polymeric polyol contain side chains.
[0007] In the polymer electrolyte of the present application, due to the alternating arrangement of segment A and segment B, the side chains of the polyol and the side chains brought by ricinoleic acid interact with each other, so that the regularity of the soft segment and the hard segment is destroyed, and the difference in the thermodynamic stability system between the soft segment and the hard segment is also reduced, so that the soft segment of the modified polyurethane and the overall crystallinity are reduced, which is beneficial to the transmission of ions. In addition, due to the alternating arrangement of segment A and segment B, the density of hydrogen bonds formed by the amino group in the hard segment and the carboxyl group of ricinoleic acid can be regulated, which ensures the mechanical strength of the polymer electrolyte while also improving the flexibility of the polymer electrolyte.
[0008] Preferably, the side chain is an alkyl side chain having 1 to 5 carbon atoms.
[0009] Preferably, the diisocyanate is one or more of isophorone diisocyanate, dicyclohexylmethane diisocyanate (MDI), hexamethylene diisocyanate (HDI), and lysine diisocyanate (LDI).
[0010] The term “one or more” as used in the present invention refers to one or a combination of two or more diisocyanates selected from the above-mentioned diisocyanates.
[0011] The second aspect of the present invention is to provide a method for preparing a polymer electrolyte, the method comprising the following steps:
[0012] S1, adding a monomer containing a side chain polyol, a diisocyanate and ricinoleic acid into a reaction vessel, and performing a pre-reaction under a protective gas;
[0013] S2, adding a chain extender and a catalyst to carry out a polymerization reaction to obtain a polymer electrolyte containing modified polyurethane;
[0014] The polyol is a polyaliphatic polyol.
[0015] The present invention adds a side chain-containing polyol and ricinoleic acid to diisocyanate at the same time. Since the isocyanate content in the system is relatively high, more ricinoleic acid can participate in the reaction, and the castor oil content in the final product is relatively high, thereby improving the flexibility, mechanical properties and low-temperature properties of the electrolyte membrane, and generating a polyurethane with high mechanical strength and good conductivity.
[0016] Preferably, the step S1 further comprises adding a viscosity control agent to reduce the viscosity; the viscosity adjuster is acetone.
[0017] Preferably, the method further comprises S3, removing acetone from the modified polyurethane after the polymerization reaction by reduced pressure distillation to obtain a modified emulsion.
[0018] Preferably, the chain extender in S2 is a hydrophilic chain extender, and the water chain extender is dimethylolpropionic acid; and the catalyst in S2 is dibutyltin diacetate.
[0019] Preferably, the polymerization reaction in S2 further comprises adding triethylamine to neutralize the remaining -COOH in the system, and then adding deionized water, stirring at high speed to complete the final chain extension reaction and emulsification.
[0020] The third aspect of the present invention is to provide a composite solid electrolyte, which includes the polymer electrolyte provided in the first aspect of the present invention, and also includes a lithium salt, wherein the lithium salt is selected from at least one of LiTFSI, LiClO4, LiBF4, LiPF6, and LiAsF6;
[0021] The mass ratio of the lithium salt to the composite solid electrolyte is 3%-12%.
[0022] Adding lithium salts to polyurethane can improve conductivity and thus improve the cycle performance of the battery.
[0023] Preferably, LATP is also included, and the LATP accounts for 1%-10% by mass of the composite solid electrolyte.
[0024] Adding LATP can significantly improve the ionic conductivity of polymer electrolytes.
[0025] The invention prepares a polymer electrolyte by reacting PPG, ricinoleic acid and IPDI to generate modified polyurethane, thereby improving the electrolyte ion conductivity and ensuring the mechanical strength of the solid electrolyte. DETAILED DESCRIPTION
[0026] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specific implementation methods are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the description and claims of the present invention and any variations thereof are intended to cover non-exclusive inclusions.
[0028] In the description of the specific implementation methods of the present invention, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present invention, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0029] Reference to "embodiments" in the present invention means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in the present invention may be combined with other embodiments.
[0030] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in the present invention generally indicates that the associated objects before and after are in an "or" relationship.
[0031] Throughout the present invention, numerical values represent approximate measures or limits of ranges to cover minor deviations from given values as well as embodiments with about the values mentioned and embodiments with the exact values mentioned. Except for the working examples provided at the end of the detailed description, all numerical values of parameters (e.g., amounts or conditions) in this specification (including the appended claims) should be understood to be modified by the term "about" in all cases, regardless of whether "about" actually appears before the numerical value. "About" indicates that the stated numerical value allows some minor imprecision (close to the exact value of the value to some extent; approximately or reasonably close to the value; almost). If the imprecision provided by "about" is not otherwise understood in this ordinary sense in the art, "about" as used in the present invention at least indicates the variation that can be produced by the ordinary methods of measuring and using such parameters. For example, "about" may include a variation of less than or equal to 5%, optionally less than or equal to 4%, optionally less than or equal to 3%, optionally less than or equal to 2%, optionally less than or equal to 1%, optionally less than or equal to 0.5%, and in some aspects, optionally less than or equal to 0.1%.
[0032] Additionally, disclosure of ranges includes disclosure of all values within the entire range and further divided ranges, including endpoints and sub-ranges given for such ranges.
[0033] Polymer electrolytes are commonly used solid electrolytes. Because their soft segments can dissolve a large amount of lithium salts and have good flexibility, they can provide good ion conductivity. The hard segments and soft segments can form hydrogen bonds. Strong hydrogen bonding provides polymer electrolytes with good mechanical properties. However, existing polyurethanes have strong room temperature crystallinity, which affects ion conductivity.
[0034] The present invention adds a polyol containing a side chain and ricinoleic acid to a diisocyanate at the same time. Since the isocyanate content in the system is relatively high, more ricinoleic acid can participate in the reaction, and the content of castor oil in the final product is relatively high, thereby improving the flexibility, mechanical properties and low-temperature properties of the electrolyte membrane, and generating a modified polyurethane with high mechanical strength and good conductivity. Specifically, since the segments A and B in the modified polyurethane are arranged alternately, the side chains of the polyol and the side chains brought by ricinoleic acid interact with each other, so that the regularity of the soft segment and the hard segment is destroyed, and the gap in the thermodynamically stable system between the soft segment and the hard segment is also reduced, so that the soft segment and the overall crystallinity of the modified polyurethane are reduced, which is conducive to the transmission of ions. In addition, due to the alternating arrangement of the segments A and B, the density of hydrogen bonds formed by the amino group in the hard segment and the carboxyl group of ricinoleic acid can be regulated, which ensures the mechanical strength of the polymer electrolyte while also improving the flexibility of the polymer electrolyte.
[0035] The embodiments of the present invention will be described in more detail below through examples and comparative examples. It should be noted that the embodiments of the present invention are not limited to these examples.
[0036] Example 1
[0037] Preparation of modified polyurethane
[0038] 1. Add isophorone diisocyanate (IPDI) into a three-necked flask, add Mn=2000 polyoxypropylene glycol (PPG) and an appropriate amount of ricinoleic acid under nitrogen protection, cooling reflux device and mechanical stirring, raise the temperature to 75°C, continue the reaction for 3 hours, and then add an appropriate amount of acetone to reduce the viscosity of the reaction system.
[0039] 2. A certain amount of dimethylolpropionic acid (DMPA) as a hydrophilic chain extender and dibutyltin diacetate (DBTDL) as a catalyst were quickly added into the reactor, the reaction temperature was lowered to 50°C, and the reaction was continued for 4 hours.
[0040] 3. Add triethylamine to neutralize the remaining -COOH in the system, then add a certain amount of deionized water, stir at high speed for 1 hour to complete the final chain extension reaction and emulsify. Finally, remove acetone by vacuum distillation to obtain a water-based polyurethane and its modified polyurethane emulsion with a solid content of about 40%.
[0041] Preparation of composite solid electrolyte membrane
[0042] 15% of LiClO4 was added to the modified polyurethane emulsion prepared above, and after being stirred and dispersed evenly, it was coated on the surface of the substrate and dried to form a solid electrolyte membrane.
[0043] Preparation of lithium-ion batteries.
[0044] The composite solid electrolyte membrane prepared above is combined with a positive electrode and a negative electrode to form a battery.
[0045] Example 2
[0046] Preparation of modified polyurethane
[0047] 1. Add isophorone diisocyanate (IPDI) into a three-necked flask, add Mn=2000 polyoxypropylene glycol (PPG) and an appropriate amount of ricinoleic acid under nitrogen protection, cooling reflux device and mechanical stirring, raise the temperature to 75°C, continue the reaction for 3 hours, and then add an appropriate amount of acetone to reduce the viscosity of the reaction system.
[0048] 2. A certain amount of dimethylolpropionic acid (DMPA) as a hydrophilic chain extender and dibutyltin diacetate (DBTDL) as a catalyst were quickly added into the reactor, the reaction temperature was lowered to 50°C, and the reaction was continued for 4 hours.
[0049] 3. Add triethylamine to neutralize the remaining -COOH in the system, then add a certain amount of deionized water, stir at high speed for 1 hour to complete the final chain extension reaction and emulsify. Finally, remove acetone by vacuum distillation to obtain a water-based polyurethane and its modified polyurethane emulsion with a solid content of about 40%.
[0050] Preparation of composite solid electrolyte membrane
[0051] 3% LiClO4 was added to the modified polyurethane emulsion prepared above, and after being stirred and dispersed evenly, it was coated on the surface of the substrate and dried to form a solid electrolyte membrane.
[0052] Preparation of lithium-ion batteries.
[0053] The composite solid electrolyte membrane prepared above is combined with a positive electrode and a negative electrode to form a battery.
[0054] Example 3
[0055] Preparation of modified polyurethane
[0056] 1. Add isophorone diisocyanate (IPDI) into a three-necked flask, add Mn=2000 polyoxypropylene glycol (PPG) and an appropriate amount of ricinoleic acid under nitrogen protection, cooling reflux device and mechanical stirring, raise the temperature to 75°C, continue the reaction for 3 hours, and then add an appropriate amount of acetone to reduce the viscosity of the reaction system.
[0057] 2. A certain amount of dimethylolpropionic acid (DMPA) as a hydrophilic chain extender and dibutyltin diacetate (DBTDL) as a catalyst were quickly added into the reactor, the reaction temperature was lowered to 50°C, and the reaction was continued for 4 hours.
[0058] 3. Add triethylamine to neutralize the remaining -COOH in the system, then add a certain amount of deionized water, stir at high speed for 1 hour to complete the final chain extension reaction and emulsify. Finally, remove acetone by vacuum distillation to obtain a water-based polyurethane and its modified polyurethane emulsion with a solid content of about 40%.
[0059] Preparation of composite solid electrolyte membrane
[0060] 6% LiClO4 was added to the modified polyurethane emulsion prepared above, and after being stirred and dispersed evenly, it was coated on the surface of the substrate and dried to form a solid electrolyte membrane.
[0061] Preparation of lithium-ion batteries.
[0062] The composite solid electrolyte membrane prepared above is combined with a positive electrode and a negative electrode to form a battery.
[0063] Example 4
[0064] Preparation of modified polyurethane
[0065] 1. Add isophorone diisocyanate (IPDI) into a three-necked flask, add Mn=2000 polyoxypropylene glycol (PPG) and an appropriate amount of ricinoleic acid under nitrogen protection, cooling reflux device and mechanical stirring, raise the temperature to 75°C, continue the reaction for 3 hours, and then add an appropriate amount of acetone to reduce the viscosity of the reaction system.
[0066] 2. A certain amount of dimethylolpropionic acid (DMPA) as a hydrophilic chain extender and dibutyltin diacetate (DBTDL) as a catalyst were quickly added into the reactor, the reaction temperature was lowered to 50°C, and the reaction was continued for 4 hours.
[0067] 3. Add triethylamine to neutralize the remaining -COOH in the system, then add a certain amount of deionized water, stir at high speed for 1 hour to complete the final chain extension reaction and emulsify. Finally, remove acetone by vacuum distillation to obtain a water-based polyurethane and its modified polyurethane emulsion with a solid content of about 40%.
[0068] Preparation of composite solid electrolyte membrane
[0069] 9% LiClO4 was added to the modified polyurethane emulsion prepared above, and after being stirred and dispersed evenly, it was coated on the surface of the substrate and dried to form a solid electrolyte membrane.
[0070] Preparation of lithium-ion batteries.
[0071] The composite solid electrolyte membrane prepared above is combined with a positive electrode and a negative electrode to form a battery.
[0072] Example 5
[0073] Preparation of modified polyurethane
[0074] 1. Add isophorone diisocyanate (IPDI) into a three-necked flask, add Mn=2000 polyoxypropylene glycol (PPG) and an appropriate amount of ricinoleic acid under nitrogen protection, cooling reflux device and mechanical stirring, raise the temperature to 75°C, continue the reaction for 3 hours, and then add an appropriate amount of acetone to reduce the viscosity of the reaction system.
[0075] 2. A certain amount of dimethylolpropionic acid (DMPA) as a hydrophilic chain extender and dibutyltin diacetate (DBTDL) as a catalyst were quickly added into the reactor, the reaction temperature was lowered to 50°C, and the reaction was continued for 4 hours.
[0076] 3. Add triethylamine to neutralize the remaining -COOH in the system, then add a certain amount of deionized water, stir at high speed for 1 hour to complete the final chain extension reaction and emulsify. Finally, remove acetone by vacuum distillation to obtain a water-based polyurethane and its modified polyurethane emulsion with a solid content of about 40%.
[0077] Preparation of composite solid electrolyte membrane
[0078] 12% LiClO4 was added to the modified polyurethane emulsion prepared above, and after being stirred and dispersed evenly, it was coated on the surface of the substrate and dried to form a solid electrolyte membrane.
[0079] Preparation of lithium-ion batteries.
[0080] The composite solid electrolyte membrane prepared above is combined with a positive electrode and a negative electrode to form a battery.
[0081] Example 6
[0082] Preparation of modified polyurethane
[0083] 1. Add isophorone diisocyanate (IPDI) into a three-necked flask, add Mn=2000 polyoxypropylene glycol (PPG) and an appropriate amount of ricinoleic acid under nitrogen protection, cooling reflux device and mechanical stirring, raise the temperature to 75°C, continue the reaction for 3 hours, and then add an appropriate amount of acetone to reduce the viscosity of the reaction system.
[0084] 2. A certain amount of dimethylolpropionic acid (DMPA) as a hydrophilic chain extender and dibutyltin diacetate (DBTDL) as a catalyst were quickly added into the reactor, the reaction temperature was lowered to 50°C, and the reaction was continued for 4 hours.
[0085] 3. Add triethylamine to neutralize the remaining -COOH in the system, then add a certain amount of deionized water, stir at high speed for 1 hour to complete the final chain extension reaction and emulsify. Finally, remove acetone by vacuum distillation to obtain a water-based polyurethane and its modified polyurethane emulsion with a solid content of about 40%.
[0086] Preparation of composite solid electrolyte membrane
[0087] 18% LiClO4 was added to the modified polyurethane emulsion prepared above, and after being stirred and dispersed evenly, it was coated on the surface of the substrate and dried to form a solid electrolyte membrane.
[0088] Preparation of lithium-ion batteries.
[0089] The composite solid electrolyte membrane prepared above is combined with a positive electrode and a negative electrode to form a battery.
[0090] Example 7
[0091] Preparation of modified polyurethane
[0092] 1. Add isophorone diisocyanate (IPDI) into a three-necked flask, add Mn=2000 polyoxypropylene glycol (PPG) and an appropriate amount of ricinoleic acid under nitrogen protection, cooling reflux device and mechanical stirring, raise the temperature to 75°C, continue the reaction for 3 hours, and then add an appropriate amount of acetone to reduce the viscosity of the reaction system.
[0093] 2. A certain amount of dimethylolpropionic acid (DMPA) as a hydrophilic chain extender and dibutyltin diacetate (DBTDL) as a catalyst were quickly added into the reactor, the reaction temperature was lowered to 50°C, and the reaction was continued for 4 hours.
[0094] 3. Add triethylamine to neutralize the remaining -COOH in the system, then add a certain amount of deionized water, stir at high speed for 1 hour to complete the final chain extension reaction and emulsify. Finally, remove acetone by vacuum distillation to obtain a water-based polyurethane and its modified polyurethane emulsion with a solid content of about 40%.
[0095] Preparation of composite solid electrolyte membrane
[0096] 15% LiClO4 and 1% LATP were added to the modified polyurethane emulsion prepared above, and after being stirred and dispersed evenly, they were coated on the surface of the substrate and dried to form a solid electrolyte membrane.
[0097] Preparation of lithium-ion batteries.
[0098] The composite solid electrolyte membrane prepared above is combined with a positive electrode and a negative electrode to form a battery.
[0099] Example 8
[0100] Preparation of modified polyurethane
[0101] 1. Add isophorone diisocyanate (IPDI) into a three-necked flask, add Mn=2000 polyoxypropylene glycol (PPG) and an appropriate amount of ricinoleic acid under nitrogen protection, cooling reflux device and mechanical stirring, raise the temperature to 75°C, continue the reaction for 3 hours, and then add an appropriate amount of acetone to reduce the viscosity of the reaction system.
[0102] 2. A certain amount of dimethylolpropionic acid (DMPA) as a hydrophilic chain extender and dibutyltin diacetate (DBTDL) as a catalyst were quickly added into the reactor, the reaction temperature was lowered to 50°C, and the reaction was continued for 4 hours.
[0103] 3. Add triethylamine to neutralize the remaining -COOH in the system, then add a certain amount of deionized water, stir at high speed for 1 hour to complete the final chain extension reaction and emulsify. Finally, remove acetone by vacuum distillation to obtain a water-based polyurethane and its modified polyurethane emulsion with a solid content of about 40%.
[0104] Preparation of composite solid electrolyte membrane
[0105] 15% LiClO4 and 2% LATP were added to the modified polyurethane emulsion prepared above, and after being stirred and dispersed evenly, they were coated on the surface of the substrate and dried to form a solid electrolyte membrane.
[0106] Preparation of lithium-ion batteries.
[0107] The composite solid electrolyte membrane prepared above is combined with a positive electrode and a negative electrode to form a battery.
[0108] Example 9
[0109] Preparation of modified polyurethane
[0110] 1. Add isophorone diisocyanate (IPDI) into a three-necked flask, add Mn=2000 polyoxypropylene glycol (PPG) and an appropriate amount of ricinoleic acid under nitrogen protection, cooling reflux device and mechanical stirring, raise the temperature to 75°C, continue the reaction for 3 hours, and then add an appropriate amount of acetone to reduce the viscosity of the reaction system.
[0111] 2. A certain amount of dimethylolpropionic acid (DMPA) as a hydrophilic chain extender and dibutyltin diacetate (DBTDL) as a catalyst were quickly added into the reactor, the reaction temperature was lowered to 50°C, and the reaction was continued for 4 hours.
[0112] 3. Add triethylamine to neutralize the remaining -COOH in the system, then add a certain amount of deionized water, stir at high speed for 1 hour to complete the final chain extension reaction and emulsify. Finally, remove acetone by vacuum distillation to obtain a water-based polyurethane and its modified polyurethane emulsion with a solid content of about 40%.
[0113] Preparation of composite solid electrolyte membrane
[0114] 15% LiClO4 and 3% LATP were added to the modified polyurethane emulsion prepared above, and after being stirred and dispersed evenly, they were coated on the surface of the substrate and dried to form a solid electrolyte membrane.
[0115] Preparation of lithium-ion batteries.
[0116] The composite solid electrolyte membrane prepared above is combined with a positive electrode and a negative electrode to form a battery.
[0117] Example 10
[0118] Preparation of modified polyurethane
[0119] 1. Add isophorone diisocyanate (IPDI) into a three-necked flask, add Mn=2000 polyoxypropylene glycol (PPG) and an appropriate amount of ricinoleic acid under nitrogen protection, cooling reflux device and mechanical stirring, raise the temperature to 75°C, continue the reaction for 3 hours, and then add an appropriate amount of acetone to reduce the viscosity of the reaction system.
[0120] 2. A certain amount of dimethylolpropionic acid (DMPA) as a hydrophilic chain extender and dibutyltin diacetate (DBTDL) as a catalyst were quickly added into the reactor, the reaction temperature was lowered to 50°C, and the reaction was continued for 4 hours.
[0121] 3. Add triethylamine to neutralize the remaining -COOH in the system, then add a certain amount of deionized water, stir at high speed for 1 hour to complete the final chain extension reaction and emulsify. Finally, remove acetone by vacuum distillation to obtain a water-based polyurethane and its modified polyurethane emulsion with a solid content of about 40%.
[0122] Preparation of composite solid electrolyte membrane
[0123] 15% LiClO4 and 4% LATP were added to the modified polyurethane emulsion prepared above, and after being stirred and dispersed evenly, they were coated on the surface of the substrate and dried to form a solid electrolyte membrane.
[0124] Preparation of lithium-ion batteries.
[0125] The composite solid electrolyte membrane prepared above is combined with a positive electrode and a negative electrode to form a battery.
[0126] Embodiment 11
[0127] Preparation of modified polyurethane
[0128] 1. Add isophorone diisocyanate (IPDI) into a three-necked flask, add Mn=2000 polyoxypropylene glycol (PPG) and an appropriate amount of ricinoleic acid under nitrogen protection, cooling reflux device and mechanical stirring, raise the temperature to 75°C, continue the reaction for 3 hours, and then add an appropriate amount of acetone to reduce the viscosity of the reaction system.
[0129] 2. A certain amount of dimethylolpropionic acid (DMPA) as a hydrophilic chain extender and dibutyltin diacetate (DBTDL) as a catalyst were quickly added into the reactor, the reaction temperature was lowered to 50°C, and the reaction was continued for 4 hours.
[0130] 3. Add triethylamine to neutralize the remaining -COOH in the system, then add a certain amount of deionized water, stir at high speed for 1 hour to complete the final chain extension reaction and emulsify. Finally, remove acetone by vacuum distillation to obtain a water-based polyurethane and its modified polyurethane emulsion with a solid content of about 40%.
[0131] Preparation of composite solid electrolyte membrane
[0132] 15% LiClO4 and 5% LATP were added to the modified polyurethane emulsion prepared above, and after being stirred and dispersed evenly, they were coated on the surface of the substrate and dried to form a solid electrolyte membrane.
[0133] Preparation of lithium-ion batteries.
[0134] The composite solid electrolyte membrane prepared above is combined with a positive electrode and a negative electrode to form a battery.
[0135] Example 12
[0136] Preparation of modified polyurethane
[0137] 1. Add isophorone diisocyanate (IPDI) into a three-necked flask, add Mn=2000 polyoxypropylene glycol (PPG) and an appropriate amount of ricinoleic acid under nitrogen protection, cooling reflux device and mechanical stirring, raise the temperature to 75°C, continue the reaction for 3 hours, and then add an appropriate amount of acetone to reduce the viscosity of the reaction system.
[0138] 2. A certain amount of dimethylolpropionic acid (DMPA) as a hydrophilic chain extender and dibutyltin diacetate (DBTDL) as a catalyst were quickly added into the reactor, the reaction temperature was lowered to 50°C, and the reaction was continued for 4 hours.
[0139] 3. Add triethylamine to neutralize the remaining -COOH in the system, then add a certain amount of deionized water, stir at high speed for 1 hour to complete the final chain extension reaction and emulsify. Finally, remove acetone by vacuum distillation to obtain a water-based polyurethane and its modified polyurethane emulsion with a solid content of about 40%.
[0140] Preparation of composite solid electrolyte membrane
[0141] 15% LiClO4 and 6% LATP were added to the modified polyurethane emulsion prepared above, and after being stirred and dispersed evenly, they were coated on the surface of the substrate and dried to form a solid electrolyte membrane.
[0142] Preparation of lithium-ion batteries.
[0143] The composite solid electrolyte membrane prepared above is combined with a positive electrode and a negative electrode to form a battery.
[0144] Embodiment 13
[0145] Preparation of modified polyurethane
[0146] 1. Add isophorone diisocyanate (IPDI) into a three-necked flask, add Mn=2000 polyoxypropylene glycol (PPG) and an appropriate amount of ricinoleic acid under nitrogen protection, cooling reflux device and mechanical stirring, raise the temperature to 75°C, continue the reaction for 3 hours, and then add an appropriate amount of acetone to reduce the viscosity of the reaction system.
[0147] 2. A certain amount of dimethylolpropionic acid (DMPA) as a hydrophilic chain extender and dibutyltin diacetate (DBTDL) as a catalyst were quickly added into the reactor, the reaction temperature was lowered to 50°C, and the reaction was continued for 4 hours.
[0148] 3. Add triethylamine to neutralize the remaining -COOH in the system, then add a certain amount of deionized water, stir at high speed for 1 hour to complete the final chain extension reaction and emulsify. Finally, remove acetone by vacuum distillation to obtain a water-based polyurethane and its modified polyurethane emulsion with a solid content of about 40%.
[0149] Preparation of composite solid electrolyte membrane
[0150] 15% LiClO4 and 7% LATP were added to the modified polyurethane emulsion prepared above, and after being stirred and dispersed evenly, they were coated on the surface of the substrate and dried to form a solid electrolyte membrane.
[0151] Preparation of lithium-ion batteries.
[0152] The composite solid electrolyte membrane prepared above is combined with a positive electrode and a negative electrode to form a battery.
[0153] Embodiment 14
[0154] Preparation of modified polyurethane
[0155] 1. Add isophorone diisocyanate (IPDI) into a three-necked flask, add Mn=2000 polyoxypropylene glycol (PPG) and an appropriate amount of ricinoleic acid under nitrogen protection, cooling reflux device and mechanical stirring, raise the temperature to 75°C, continue the reaction for 3 hours, and then add an appropriate amount of acetone to reduce the viscosity of the reaction system.
[0156] 2. A certain amount of dimethylolpropionic acid (DMPA) as a hydrophilic chain extender and dibutyltin diacetate (DBTDL) as a catalyst were quickly added into the reactor, the reaction temperature was lowered to 50°C, and the reaction was continued for 4 hours.
[0157] 3. Add triethylamine to neutralize the remaining -COOH in the system, then add a certain amount of deionized water, stir at high speed for 1 hour to complete the final chain extension reaction and emulsify. Finally, remove acetone by vacuum distillation to obtain a water-based polyurethane and its modified polyurethane emulsion with a solid content of about 40%.
[0158] Preparation of composite solid electrolyte membrane
[0159] 15% LiClO4 and 8% LATP were added to the modified polyurethane emulsion prepared above, and after being stirred and dispersed evenly, they were coated on the surface of the substrate and dried to form a solid electrolyte membrane.
[0160] Preparation of lithium-ion batteries.
[0161] The composite solid electrolyte membrane prepared above is combined with a positive electrode and a negative electrode to form a battery.
[0162] Embodiment 15
[0163] Preparation of modified polyurethane
[0164] 1. Add isophorone diisocyanate (IPDI) into a three-necked flask, add Mn=2000 polyoxypropylene glycol (PPG) and an appropriate amount of ricinoleic acid under nitrogen protection, cooling reflux device and mechanical stirring, raise the temperature to 75°C, continue the reaction for 3 hours, and then add an appropriate amount of acetone to reduce the viscosity of the reaction system.
[0165] 2. A certain amount of dimethylolpropionic acid (DMPA) as a hydrophilic chain extender and dibutyltin diacetate (DBTDL) as a catalyst were quickly added into the reactor, the reaction temperature was lowered to 50°C, and the reaction was continued for 4 hours.
[0166] 3. Add triethylamine to neutralize the remaining -COOH in the system, then add a certain amount of deionized water, stir at high speed for 1 hour to complete the final chain extension reaction and emulsify. Finally, remove acetone by vacuum distillation to obtain a water-based polyurethane and its modified polyurethane emulsion with a solid content of about 40%.
[0167] Preparation of composite solid electrolyte membrane
[0168] 15% LiClO4 and 9% LATP were added to the modified polyurethane emulsion prepared above, and after being stirred and dispersed evenly, they were coated on the surface of the substrate and dried to form a solid electrolyte membrane.
[0169] Preparation of lithium-ion batteries.
[0170] The composite solid electrolyte membrane prepared above is combined with a positive electrode and a negative electrode to form a battery.
[0171] Example 16
[0172] Preparation of modified polyurethane
[0173] 1. Add isophorone diisocyanate (IPDI) into a three-necked flask, add Mn=2000 polyoxypropylene glycol (PPG) and an appropriate amount of ricinoleic acid under nitrogen protection, cooling reflux device and mechanical stirring, raise the temperature to 75°C, continue the reaction for 3 hours, and then add an appropriate amount of acetone to reduce the viscosity of the reaction system.
[0174] 2. A certain amount of dimethylolpropionic acid (DMPA) as a hydrophilic chain extender and dibutyltin diacetate (DBTDL) as a catalyst were quickly added into the reactor, the reaction temperature was lowered to 50°C, and the reaction was continued for 4 hours.
[0175] 3. Add triethylamine to neutralize the remaining -COOH in the system, then add a certain amount of deionized water, stir at high speed for 1 hour to complete the final chain extension reaction and emulsify. Finally, remove acetone by vacuum distillation to obtain a water-based polyurethane and its modified polyurethane emulsion with a solid content of about 40%.
[0176] Preparation of composite solid electrolyte membrane
[0177] 15% LiClO4 and 10% LATP were added to the modified polyurethane emulsion prepared above, and after being stirred and dispersed evenly, they were coated on the surface of the substrate and dried to form a solid electrolyte membrane.
[0178] Preparation of lithium-ion batteries.
[0179] The composite solid electrolyte membrane prepared above is combined with a positive electrode and a negative electrode to form a battery.
[0180] Comparative Example 1
[0181] Preparation of modified polyurethane
[0182] 1. Add isophorone diisocyanate (IPDI) into a three-necked flask, add polyethylene glycol (PEG) with Mn=2000 and an appropriate amount of ricinoleic acid under nitrogen protection, cooling reflux device and mechanical stirring, raise the temperature to 75°C, continue the reaction for 3 hours, and then add an appropriate amount of acetone to reduce the viscosity of the reaction system.
[0183] 2. A certain amount of dimethylolpropionic acid (DMPA) as a hydrophilic chain extender and dibutyltin diacetate (DBTDL) as a catalyst were quickly added into the reactor, the reaction temperature was lowered to 50°C, and the reaction was continued for 4 hours.
[0184] 3. Add triethylamine to neutralize the remaining -COOH in the system, then add a certain amount of deionized water, stir at high speed for 1 hour to complete the final chain extension reaction and emulsify. Finally, remove acetone by vacuum distillation to obtain a water-based polyurethane and its modified polyurethane emulsion with a solid content of about 40%.
[0185] Preparation of composite solid electrolyte membrane
[0186] 3% LiClO4 was added to the modified polyurethane emulsion prepared above, and after being stirred and dispersed evenly, it was coated on the surface of the substrate and dried to form a solid electrolyte membrane.
[0187] Preparation of lithium-ion batteries.
[0188] The composite solid electrolyte membrane prepared above is combined with a positive electrode and a negative electrode to form a battery.
[0189] Comparative Example 2
[0190] Preparation of modified polyurethane
[0191] 1. Add isophorone diisocyanate (IPDI) into a three-necked flask, add Mn=2000 polyoxypropylene glycol (PPG) under nitrogen protection, cooling reflux device and mechanical stirring, raise the temperature to 75°C, continue the reaction for 3 hours, and then add an appropriate amount of acetone to reduce the viscosity of the reaction system.
[0192] 2. A certain amount of dimethylolpropionic acid (DMPA) as a hydrophilic chain extender and dibutyltin diacetate (DBTDL) as a catalyst were quickly added into the reactor, the reaction temperature was lowered to 50°C, and the reaction was continued for 4 hours.
[0193] 3. Add triethylamine to neutralize the remaining -COOH in the system, then add a certain amount of deionized water, stir at high speed for 1 hour to complete the final chain extension reaction and emulsify. Finally, remove acetone by vacuum distillation to obtain a water-based polyurethane and its modified polyurethane emulsion with a solid content of about 40%.
[0194] Preparation of composite solid electrolyte membrane
[0195] 3% LiClO4 was added to the modified polyurethane emulsion prepared above, and after being stirred and dispersed evenly, it was coated on the surface of the substrate and dried to form a solid electrolyte membrane.
[0196] Preparation of lithium-ion batteries.
[0197] The composite solid electrolyte membrane prepared above is combined with a positive electrode and a negative electrode to form a battery.
[0198] Comparative Example 3
[0199] Preparation of modified polyurethane
[0200] 1. Add isophorone diisocyanate (IPDI) into a three-necked flask. Under nitrogen protection, cooling reflux device and mechanical stirring, add appropriate amount of ricinoleic acid, raise the temperature to 75°C, continue the reaction for 3 hours, and then add appropriate amount of acetone to reduce the viscosity of the reaction system.
[0201] 2. A certain amount of dimethylolpropionic acid (DMPA) as a hydrophilic chain extender and dibutyltin diacetate (DBTDL) as a catalyst were quickly added into the reactor, the reaction temperature was lowered to 50°C, and the reaction was continued for 4 hours.
[0202] 3. Add triethylamine to neutralize the remaining -COOH in the system, then add a certain amount of deionized water, stir at high speed for 1 hour to complete the final chain extension reaction and emulsify. Finally, remove acetone by vacuum distillation to obtain a water-based polyurethane and its modified polyurethane emulsion with a solid content of about 40%.
[0203] Preparation of composite solid electrolyte membrane
[0204] 3% LiClO4 was added to the modified polyurethane emulsion prepared above, and after being stirred and dispersed evenly, it was coated on the surface of the substrate and dried to form a solid electrolyte membrane.
[0205] Preparation of lithium-ion batteries.
[0206] The composite solid electrolyte membrane prepared above is combined with a positive electrode and a negative electrode to form a battery.
[0207] Comparative Example 4
[0208] Preparation of modified polyurethane
[0209] 1. Add isophorone diisocyanate (IPDI) into a three-necked flask, add Mn=2000 polyoxypropylene glycol (PPG) under nitrogen protection, cooling reflux device and mechanical stirring, and heat to 75°C. After the reaction is continued for 3 hours, add an appropriate amount of acetone to reduce the viscosity of the reaction system.
[0210] 2. A certain amount of dimethylol propionic acid (DMPA) as a hydrophilic chain extender and dibutyl tin diacetate (DBTDL) as a catalyst were quickly added into the reactor, the reaction temperature was lowered to 50°C, and the reaction was continued for 4 hours. After completion, an appropriate amount of ricinoleic acid was added.
[0211] 3. Add triethylamine to neutralize the remaining -COOH in the system, then add a certain amount of deionized water, stir at high speed for 1 hour to complete the final chain extension reaction and emulsify. Finally, remove acetone by vacuum distillation to obtain a water-based polyurethane and its modified polyurethane emulsion with a solid content of about 40%.
[0212] Preparation of composite solid electrolyte membrane
[0213] 3% LiClO4 was added to the modified polyurethane emulsion prepared above, and after being stirred and dispersed evenly, it was coated on the surface of the substrate and dried to form a solid electrolyte membrane.
[0214] Preparation of lithium-ion batteries.
[0215] The composite solid electrolyte membrane prepared above is combined with a positive electrode and a negative electrode to form a battery.
[0216] Comparative experiment
[0217] A total of 20 groups of samples from Examples 1-16 and Comparative Examples 1-4 were used to conduct battery cycle performance tests, solid electrolyte membrane ion conductivity tests, and mechanical strength tests. The test results were averaged, and the number of samples in each group was 20.
[0218] The battery cycle performance test method steps are as follows:
[0219] A1, at room temperature, the sample was discharged at a current of 1 / 10C to a discharge termination voltage of 2.75V;
[0220] A2, set aside for 10 min;
[0221] A3, at room temperature, charge the sample to 4.25V at a current of 1 / 10C, then switch to constant voltage charging, with the end current at 0.05C
[0222] A4, set aside for 10 min;
[0223] A5, at room temperature, discharge at 1 / 10C current to a termination voltage of 2.75V, and record the discharge capacity;
[0224] A6, step A2 to step A5 are cycled continuously until the number of cycles reaches the required number or the discharge capacity is lower than 80% of the initial capacity (remaining capacity / initial discharge capacity), then the test is terminated.
[0225] Solid electrolyte membrane ion conductivity test method:
[0226] B1, electrochemical selection IMP mode at room temperature;
[0227] B2, frequency range 0.1~1MHz, disturbance amplitude 10mV;
[0228] B3, the impedance Re of the solid electrolyte membrane obtained by testing;
[0229] B4, based on the impedance, thickness d and area S of the solid electrolyte membrane, the conductivity σ of the solid electrolyte membrane is calculated.
[0230]
[0231] Where d is the thickness of the sample under test (cm); Re is the body impedance of the sample under test (ohm), which can be obtained from the intersection of the semicircle and the oblique line in the Nyquist plot of the electrochemical impedance spectrum; S is the effective area of the solid electrolyte membrane (cm2).
[0232] The mechanical strength test method adopts the traditional lithium-ion battery mechanical strength test method.
[0233] The test results are shown in the following table:
[0234]
[0235]
[0236]
[0237] According to Examples 1-4 in the above table, the more lithium salt is contained in the composite solid electrolyte, the higher the battery cycle life, ionic conductivity and mechanical strength will be. This indicates that the increase of lithium salt can effectively improve the ionic conductivity and battery cycle performance.
[0238] According to Example 1, Example 5 and Example 6 in the above table, when the proportion of lithium salt increases within a certain range, although the battery ion conductivity and mechanical strength will increase, the battery cycle life will decrease. When the proportion of lithium salt exceeds a certain range, not only will the battery ion conductivity decrease, but the battery cycle life will also decrease. This shows that the more lithium salt the better, but within a certain range, the more lithium salt the better.
[0239] Combining the experimental data of Examples 1-6, it can be seen that by controlling the proportion of lithium salt in the composite solid electrolyte, a battery with good ion conductivity, mechanical strength and battery cycle life can be obtained.
[0240] According to Example 1 and Example 7 in the above table, it can be seen that adding a small amount of LATP to the composite solid electrolyte can significantly improve the ionic conductivity and battery cycle performance of the polymer electrolyte.
[0241] According to Examples 7-11 in the above table, when the proportion of LATP in the composite solid electrolyte increases, the battery's cycle performance, ionic conductivity and mechanical strength will increase accordingly. This further proves that LATP can significantly improve the ionic conductivity of polymer electrolytes and the effect of battery cycle performance.
[0242] According to Examples 11-16 in the above table, when the proportion of LATP in the composite solid electrolyte exceeds a certain range, the battery cycle performance will not be further improved, but the ionic conductivity will continue to increase.
[0243] According to Examples 1-16 in the above table, it can be seen that by adjusting the ratio of LATP and lithium salt in the composite solid electrolyte, a battery that takes into account ionic conductivity, mechanical strength and battery cycle life can be obtained. For example, Example 16.
[0244] According to Example 2 and Comparative Example 1, after PPG was replaced with PEG, the battery cycle performance and ionic conductivity were significantly reduced. This shows that compared with polyethylene glycol, polyols can effectively improve the battery cycle performance and ionic conductivity.
[0245] According to Example 2 and Comparative Example 2, after ricinoleic acid was removed from the composite solid electrolyte, the battery cycle performance, ion conductivity and mechanical strength all decreased significantly. This shows that ricinoleic acid is indispensable to improve battery cycle performance, ion conductivity and mechanical strength.
[0246] According to Example 2 and Comparative Example 3, after the composite solid electrolyte abandoned the polyol, the battery cycle performance, ion conductivity and mechanical strength all decreased significantly. This shows that polyol is indispensable to improve the battery cycle performance, ion conductivity and mechanical strength.
[0247] According to Example 2 and Comparative Example 4, when preparing modified polyurethane, if ricinoleic acid is added after catalysis, the battery's cycle performance, ion conductivity and mechanical strength will all decrease. This shows that in order to improve the battery's cycle performance, ion conductivity and mechanical strength, ricinoleic acid must participate in the entire process of the formation reaction of modified polyurethane.
[0248] It should be pointed out that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A polymer electrolyte, characterized in that The modified polyurethane comprises a segment A of a polyol and a segment B formed by the reaction of a diisocyanate and ricinoleic acid, wherein the segment A and the segment B are arranged alternately; Wherein, the polyol is a polyaliphatic polyol; The monomers of the polymeric polyol contain side chains.
2. The polymer electrolyte according to claim 1, characterized in that The side chain is an alkyl side chain having 1 to 5 carbon atoms.
3. The polymer electrolyte according to claim 1, characterized in that The diisocyanate is one or more of isophorone diisocyanate, dicyclohexylmethane diisocyanate (MDI), hexamethylene diisocyanate (HDI), and lysine diisocyanate (LDI).
4. A method for preparing a polymer electrolyte, characterized in that: The steps include: S1, adding a monomer containing a side chain polyol, a diisocyanate and ricinoleic acid into a reaction vessel, and performing a pre-reaction under a protective gas; S2, adding a chain extender and a catalyst to carry out a polymerization reaction to obtain a polymer electrolyte containing modified polyurethane; The polyol is a polyaliphatic polyol.
5. The method according to claim 4, characterized in that In the S1, a viscosity control agent is added to reduce the viscosity; the viscosity adjuster is acetone.
6. The method according to claim 5, characterized in that The method further comprises S3, removing acetone from the modified polyurethane after the polymerization reaction by reduced pressure distillation to obtain a modified emulsion.
7. The method according to claim 4, characterized in that The chain extender in S2 is a hydrophilic chain extender, and the water chain extender is dimethylol propionic acid; the catalyst in S2 is dibutyltin diacetate.
8. The method according to claim 4, characterized in that The polymerization reaction in S2 further includes adding triethylamine to neutralize the remaining -COOH in the system, and then adding deionized water, stirring at high speed to complete the final chain extension reaction and emulsification.
9. A composite solid electrolyte, comprising the modified polyurethane polymer electrolyte according to any one of claims 1 to 3, characterized in that: Also includes a lithium salt, the lithium salt is selected from at least one of LiTFSI, LiClO4, LiBF4, LiPF6, and LiAsF6; The mass ratio of the lithium salt to the composite solid electrolyte is 3%-12%.
10. The composite solid electrolyte according to claim 9, characterized in that: It also includes LATP, and the mass ratio of the LATP to the composite solid electrolyte is 1%-10%.